2005
DOI: 10.1002/dmrr.599
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of the vanilloid receptor 1 (TRPV1) is altered by long‐term diabetes in epineurial arterioles of the rat sciatic nerve

Abstract: These studies suggest that long-term diabetes causes vascular dysfunction in epineurial arterioles of the sciatic nerve that includes a decrease in capsaicin-induced vasoconstriction that is likely due to a decrease in the expression of vanilloid receptor 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…6,20,21 DM might interfere with the expression of TRPV1 as several investigations have found that the expression of TRPV1 in DRG and epineurial arterioles was decreased in diabetic animals. 9,10 In the previous and present study, we disclosed in each that the expression of both TRPV1 and CGRP in diabetic mouse hearts is markedly reduced in comparison with that in the non-diabetic hearts, implying that the function of TRPV1 in the heart was impaired by diabetes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…6,20,21 DM might interfere with the expression of TRPV1 as several investigations have found that the expression of TRPV1 in DRG and epineurial arterioles was decreased in diabetic animals. 9,10 In the previous and present study, we disclosed in each that the expression of both TRPV1 and CGRP in diabetic mouse hearts is markedly reduced in comparison with that in the non-diabetic hearts, implying that the function of TRPV1 in the heart was impaired by diabetes.…”
Section: Discussionsupporting
confidence: 55%
“…9 Using immunohistochemical staining, TRPV1 was also found to be reduced in epineurial arterioles in long-term diabetic rats. 10 These investigations suggest that the expression of TRPV1 is susceptible to diabetes. In addition, recent studies disclose that TRPV1 is expressed in the myocardium and perivascular region, which are close to the epicardial surface of ventricles.…”
mentioning
confidence: 97%
“…Decreased TRPV1 expression in diabetic animals has been previously reported (7). However, the impact of decreased TRPV1 channel expression on the diabetic heart has not been thoroughly investigated.…”
Section: H221 Vascular Trpv1 Channels In Type II Diabetesmentioning
confidence: 92%
“…We and others (1,3,7,10,31,41,43) have revealed TRP channel expression in vascular smooth muscle cells (VSMC) and endothelial cells (EC) suggesting these channels regulate vascular functions. Specifically, we found that TRPV1 channels play an important role in the vascular reactivity, largely through Ca 2ϩ entry via endothelial TRPV1 channels, triggering nitric oxide (NO)-dependent vasodilation in endothelium of conduit coronary arteries from Ossabaw swine (3).…”
mentioning
confidence: 97%
“…The precise mechanisms underlying this beneficial effect of capsaicin in diabetic patients remain to be determined. Diabetic neuropathy is known to be associated with a reduced production of CGRP, a vasoactive molecule that is under the control of TRPV1 receptors in nerve terminals, and causes neurogenic vasodilation (11). Activation of TRPV1 by capsaicin may cause an increased CGRP release, thereby restoring the blood vessel response to stimulation of sensory nerve endings (12).…”
Section: Discussionmentioning
confidence: 99%